Urethral Large Hemangioma in a Prepubertal Female Patient – A Case Report - Uddin, Nasir; Kakan, Fahmida Bayes; Hasan, M M; Amin, Ruhul; Hossain, Sarwar; Sarkar, Israfil (Journal of Comilla Medical College Teachers' Association, 2023)
Background: Hemangiomas rarely occur in the urethra, and most reported cases have involved in men and elderly women1-4. The clinical manifestations of urethral hemangiomas include lower urinary tract symptoms, dysuria, hematuria, perineal discomfort, and urethral discharge. There are only a few cases reported in the literature and exact incidence is still not known.1-5 A few case reports and occasional series have described posterior urethral hemangioma presenting as hematuria. We are reporting a rare case of a cavernous hemangioma of the anterior urethra in a prepubertal female who presented in the gynae OPD with bleeding per vagina. J Com Med Col Teachers Asso Jan 2023; 27(1): 42-43